2013
DOI: 10.1155/2013/395316
|View full text |Cite
|
Sign up to set email alerts
|

The Herbal DrugMelampyrum pratenseL. (Koch): Isolation and Identification of Its Bioactive Compounds Targeting Mediators of Inflammation

Abstract: Melampyrum pratense L. (Koch) is used in traditional Austrian medicine for the treatment of different inflammation-related conditions. In this work, we show that the extracts of M. pratense stimulated peroxisome proliferator-activated receptors- (PPARs-)α and -γ that are well recognized for their anti-inflammatory activities. Furthermore, the extract inhibited the activation of the proinflammatory transcription factor NF-κB and induction of its target genes interleukin-8 (IL-8) and E-selectin in vitro. Bioassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…The following approximate quantitative content of individual main flavonoids was calculated: 12% of hyperoside, 10% of cinaroside, less than 1% of apigenin and of luteolin. The last two components are poorly soluble in water and their concentration is reported to be higher in the ethanol extracts of Melampyrum pratense (Galishevskaya and Petrichenko, 2010;Suchinina et al, 2010;Vogl et al, 2013).…”
Section: Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…The following approximate quantitative content of individual main flavonoids was calculated: 12% of hyperoside, 10% of cinaroside, less than 1% of apigenin and of luteolin. The last two components are poorly soluble in water and their concentration is reported to be higher in the ethanol extracts of Melampyrum pratense (Galishevskaya and Petrichenko, 2010;Suchinina et al, 2010;Vogl et al, 2013).…”
Section: Extractionmentioning
confidence: 99%
“…It was found that the density of the air-dried stock of Mp ranges from 76713 to 240723 kg/ha. Biological stock ranges from 3.2 to 4 t, and the operating stock is about Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jep 2.9 t. According to some studies Mp may affect the nervous system (Galishevskaya and Petrichenko, 2010;Vogl et al, 2013). Due to their unique properties, these plants are widely used in folk medicine as sedatives and anticonvulsants (Sokolov, 1990;Galishevskaya and Petrichenko, 2010;Vogl et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations